Public perception towards landscape of conflict: a preliminary study on historic battlefield preservation in Malaysia - Abu Bakar, Shamsul; Ahmad Sahimi, Mohd Suhail; Mohamed Saleh, Rahayu (Universiti Putra Malaysia Press, 2020)
Landscapes of conflict in Malaysia are currently under constant threats from the urbanization process and often permanently lose its historical characteristics. Besides the need for appropriate legislation to protect this type of cultural resources, public understanding, and awareness regarding the battlefield landscape’s importance may also contribute towards its future existence. This study employed an on-site questionnaire survey to identify the public perception of the historic battlefield landscape. A total of 60 respondents participated in the survey conducted at the Muzium Tentera Darat (Army Museum) in Port Dickson. The survey offers positive insights into the level of public awareness, essential elements, and design recommendations for future battlefield landscape preservation. The study also revealed that religious and mystical phenomena typically associated with deadly spaces are not public issues.